(3GdSeW GdKejf aj efGbH CegGJ GdeDefjfs - (3eMH GdOjf GdWHQj , CMeO Hf YHO Gddg Hf eMeO GdWHQj,J (B694 (3g` s ((3Ydi Hf CHj HcQ Hf YjSi Hf GdQUGU GdMfai s)
(3ChdgG (B:s
(3GdMeO ddg ceG jfHZi dYXje LdGdg CeG HYO agPG eDda QSeJg HGdSeW GdKejf s
(3BNQgG (B:s
(3Ke GYJbgG adMbJ HCgdgG PcQ Pdc CHh YeQh hUGMH GdUahI gPG BNQ eG GfJgi Edjg LeYfG faY Gddg Hg agPG cJGH GdSeW GdWHQi GdTGei s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B159 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B298s
Keywords: (3GdJGQjNs